Integrated genetic evaluation of breeding field test traits, competition traits and test status in Icelandic horses - Elsa Albertsdóttir 1975- (2010)
The main goal in breeding the Icelandic horse is to produce aesthetically appealing and capable riding horses with five gaits and good spirit, suited both for leisure and competition. Selection of Icelandic breeding horses is based on breeding values calculated from the breeding field test records. It has been speculated that assessed horses are not a random sample of the population, a situation that would lead to bias in estimated breeding values and retards genetic improvement. The main aim of this thesis was to study integrated genetic evaluation of competition traits and breeding field test traits for Icelandic horses where the effects of preselection in the data were accounted for. Genetic parameters of the competition traits, and of genetic relationships between competition traits and the breeding field test traits were analysed. The breeding field test data included individual records of Icelandic horses evaluated in 11 countries. The competition data included records of horses that had competed in Iceland and Sweden. The competition traits and breeding field test traits were analysed using linear animal models. The competition traits analysed were both original and combined ones covering the competition aptitude of four-gait, five-gait, toelt and pace. The combined traits were formed in order to describe the competition traits in a simpler manner. The estimated heritabilities were low to moderately high for all competition traits and the genetic correlations estimated among competition traits were generally strong and favourable with few exceptions. Moderate genetic correlations were estimated between most of the competition traits and some of the conformation traits assessed at breeding field tests. High genetic correlations were generally estimated between the competition traits and most of the riding ability traits recorded in breeding field tests. Competition traits were concluded to be suitable for genetic selection. Breeding field test traits and test status, an all-or-none trait describing ...